CONTENTIOUS POLITICS IN A REMOTE AREA OF THE MOLLUCAN ARCHIPELAGO - masnun, leolita (Masyarakat Indonesia, 2023)
The central question of this dissertation is How has contentious politics developed in Maluku Barat Daya as a remote area in Indonesia since Reformasi? This study has resulted in a portrait of the political processes driving the successive splitting of local governments in the southernmost region of the Moluccan Archipelago. It leads to the conclusion that, although Reformasi and Otonomi Daerah might have been the direct cause of the current dynamic, continuous contentious politics in Kabupaten Maluku Barat Daya/MBD (Southwest Maluku Regency) and the southernmost region of the Maluku offer a better explanation of the dynamic political process. I have developed an anthropological understanding of the capacities and practices summoned up by local people in their responses to the external opportunities offered by the national institutional setting and of their capacity to create the opportunity to make socio-political changes themselves. The research methods and tools that I used to collect data are participant observation, interviews and secondary data collection in literature searches, archives, news in newspapers and information spread on social media. I did fieldwork in Indonesia for twelve months in total from the end of February 2018 to February 2019. In this dissertation, I have presented my research findings in a chronological order of the occurrences of contentious politics in the southernmost region of Maluku for over seventy years. I have adopted the term pemekaran to delineate each political process of the eruptions of contentious politics which occurred between 1950 to 1999, 1999 to 2008, and 2008 to 2018.